Durch Europäisierung zu mehr Durchlässigkeit? Veränderungsdynamiken des Verhältnisses von beruflicher Bildung zur Hochschulbildung in Deutschland und Frankreich - Bernhard, Nadine (Verlag Barbara Budrich, 2017)
Life chances today are increasingly determined by school, vocational, university and further education. The author examines the permeability between vocational and higher education - an important prerequisite for enabling participation in education and society - in comparison between Germany and France. The focus is on stability and change at the institutional level and the influence of European educational processes since the end of the 1990s as well as their re-/productive significance in relation to social educational inequalities. Awarded the Young Investigators' Prize for Sociology of Education by the Education Section of the German Society for Sociology.